Characterization and Phylogenetic Analysis of a Novel GH43 β-Xylosidase From Neocallimastix californiae - Stabel, Marcus; Hagemeister, Julia; Heck, Zacharias; Aliyu, Habibu; Ochsenreither, Katrin (Frontiers in Fungal Biology, 2021)
Degradation of lignocellulosic materials to release fermentable mono- and disaccharides is a decisive step towards a sustainable bio-based economy, thereby increasing the demand of robust and highly active lignocellulolytic enzymes. Anaerobic fungi of the phylum Neocallimastigomycota are potent biomass degraders harboring a huge variety of such enzymes. Compared to cellulose, hemicellulose degradation has received much less attention; therefore, the focus of this study has been enzymatic xylan degradation. We report the heterologous expression of a GH43 xylosidase, Xyl43Nc, and a GH11 endoxylanase, X11Nc, from the anaerobic fungus Neocallimastix californiae in Escherichia coli. The enzymes were identified by screening of the putative proteome. Xyl43Nc was highly active against 4-Nitrophenol-xylopyranosides with a Km of 0.72 mM, a kcat of 29.28 s-1, a temperature optimum of 32 °C and a pH optimum of 6. When combined, Xyl43Nc and X11Nc released xylose from beechwood xylan and arabinoxylan from wheat. Phylogenetic analysis revealed that Xyl43Nc shares common ancestry with enzymes from Spirochaetes and groups separately from Ascomycete sequences in our phylogeny, highlighting the importance of horizontal gene transfer in in the evolution of the anaerobic fungi.